Differences in the Morphological Characteristics and Body Composition of Football Players in Montenegro - Marin Corluk; Ivan Vasiljevic (Journal of Anthropology of Sport and Physical Education)
The aim of this research was to determine the differences among the top football players of the two best Montenegrin club FC Sutjeska-Niksic and FC Budućnost-Podgorica in the morphological characteristics and body composition. A sample of 53 examinees is divided into two sub-samples. The first sub-sample of the examinees consisted of 23 players of FC Sutjeska-Niksic of the average age of 21.69 ± 4.30, the champions of the Cup of Montenegro in the season 2016/17, while the other sub-sample consisted of 30 players of FC Budućnost-Podgorica of the average age 22.73 ± 4.33, the champions of the Montenegrin Championship in the season 2016/17. Football players were tested immediately after the end of the competition season 2016/17. Morphological characteristics in the body composition were evaluated by a battery of 11 variables: body height, body weight, waist size, triceps skin set, biceps skin set, back skin set, abdominal skin set, body mass index, fat percentage, muscle mass and bone mass. The standard central and dispersive parameters of all variables are calculated. The significance of the differences between the players of the top two football clubs in the morphological characteristics and variables for assessing body composition was determined by a t-test for independent samples. It was found that the football players of the two mentioned clubs have statistically significant differences by the variables that estimate the amount of subcutaneous fat tissue.